Comparative Analysis of the Use of Renewable Energy Sources in Selected Countries - Reljić, Marija M; Mihić, Marko; Cvijović, Jelena (Industrija, 2018)
The aim of the paper is to present the results of a comparative analysis of energy consumption from renewable sources in total energy consumption in four European countries - Italy, Norway, Ukraine and Serbia. The research is based on the analysis of scientific literature and secondary data sources. Based on a comprehensive literature review and analysis of statistical data from this area, the answer to the research question is:  How much is the use of renewable energy sources (RES) in selected European countries, which sources of RES are used,  in which sectors of the economy and who are socio-economic effects of RES use. In addition, brief overviews of the framework and incentive measures that are applied in selected countries are presented in order to stimulate the use of renewable energy sources.
Keywords: Use of RES; Socio-economic effects; Renewable energy sources; Energy consumption; Analysis